A note on the existence and global stability of deformations of compressible nonlinearly elastic solids (Archives of Mechanics - Test, 2001)
The existence and global stability of certain deformations of isotropic compressible hyperelastic solids is investigated for the case when the body forces are zero and boundary conditions of place are satisfied. Certain global stability results are obtained and, using a phase-plane analysis, the existence of deformations describing the bending of rectangular blocks into annular cylindrical sectors is established.